THE IMPACT OF PROJECT BASED LEARNING ‘WEEBLY BLOG’ ON STUDENTS’ ABILITY OF OFFERING OPINION IN SOCIAL SCIENCE LEARNING - Rezkhikha, Rayindayu Dwi (Universitas Pendidikan Indonesia, 2019)
This study was motivated by the low skill of expressing opinions in class VIII SMP Negeri 5 Bandung because students tend to participate less actively in in expressing opinions. The methods used in this research was quasi-experimental using the Nonequivalent Control Group Design. The purpose of this study were to know the impact of the project based learning Weebly Blog on the offering opinion skill in experimental class and control class. This study sample was taken with purposive sampling technique. Data collection techniques used in this study were essay tests and questionnaires. The researcher employed Kolmogorov-Smirnov test of normality as an analysis technique and hypothesis testing with t-test. The results showed that there was no significant difference between the results of the study in the experimental class and the control class. It is known based on the acquisition of sig. (2-tailed), the average value of the experimental class pre-test of 57.6, while the control class is 64.7. After being given treatment, both of them get 68. Based on the statistical data processing, the average value of the experimental class was not able to achieve greater acquisition of the control class. That is, the implementation of Weebly Blog project-based learning is not effective in improving opinion skills compared to the application of portfolio-based project learning.Keywords: Project Based Learning, Weebly Blog, Offering Opinion Skill.